Implementation Education Analysis Study Of Workload And Work Life Quality On Teacher Performance Through Financial Compensation As An Intervening Variable - Hasanah, Uswatun; Ismail, Iriani (Edumaspul: Jurnal Pendidikan, 2023)
This research is motivated by the performance of elementary school teachers in Galis Subdistrict that is not aligned with the growing workload and the impact on the work life quality of these teachers. The aim of this study is to determine the influence of (1) Workload on Performance, (2) Work life quality on performance, (3) Financial compensation on Performance, (4) Workload on financial compensation, (5) Work life quality on financial compensation, (6) Workload on teacher performance in Galis Subdistrict through financial compensation as an intervening variable, (7) Work life quality on teacher performance in Galis Subdistrict through financial compensation as an intervening variable. The data used as samples in this research are the results of observations and questionnaires using the random sampling method. The questionnaire values are disclosed using a Likert scale of 1-5. The analysis method in this research employs Structural Equation Modeling (SEM) using the SmartPLS application. The results of this study indicate that (1) Workload has a positive and significant impact on performance. (2) Work life quality has a positive and significant impact on performance. (3) Workload has a positive and significant impact on financial compensation. (4) Work life quality has a positive and significant impact on financial compensation. (5) Financial compensation has a positive and significant impact on performance. (6) Workload has a positive and significant impact on teacher performance in Galis Subdistrict through financial compensation as an intervening variable. (7) Work life quality has a positive and significant impact on teacher performance in Galis Subdistrict through financial compensation as an intervening variable.